Cross-Cultural Adaptation and Validation of the Chinese Version of the Brace Questionnaire - Yi, Honglei; Chen, Hu; Wang, Xinhui; Xia, Hong (Frontiers in Pediatrics, 2022)
Objective: To adapt the questionnaire cross-culturally and to analyze the adaptation and validation of the Chinese version of the Brace Questionnaire (C-BrQ). Methods: The adaptation was based on the International Quality of Life Assessment Project guidelines. A total of 79 patients with AIS were included to examine the psychometric properties of the C-BrQ. The reliability was assessed using internal consistency (the Cronbach's alpha coefficient) and test–retest reliability (intraclass correlation coefficient ICC2.1, 95% CI). Floor and ceiling effects were calculated. Lin's concordance correlation coefficient (CCC, 95% CI) was used to compare the agreement between the Scoliosis Research Society-22 patient questionnaire (SRS-22) and C-BrQ. Results: There were strong correlations between each item and its corresponding domain significantly. The correlations between the C-BrQ domains and their related questions vary from moderate to strong (r = 0.311–0.933, P < 0.05). The Cronbach's was 0.891, showing good internal consistency of each domain of the BrQ, and the ICC in test–retest was 0.860 (0.8776, 0.912), which means an excellent test–retest reliability. The Lin's CCC between SRS-22 and C-BrQ was 0.773 (0.669, 0.848), showing great agreement. However, no significant floor and ceiling effects in C-BrQ was observed except the ceiling effect in school activity and bodily pain. Conclusion: BrQ was translated and cross-culturally adapted for use in China with good internal consistency and excellent test–retest reliability.